FUNDAMENTALS OF SPEAKER RECOGNITION - Figen ERTAŞ (Pamukkale University Journal of Engineering Sciences, 2000)
The explosive growth of information technology in the last decade has made a considerable impact on the design and construction of systems for human-machine communication, which is becoming increasingly important in many aspects of life. Amongst other speech processing tasks, a great deal of attention has been devoted to developing procedures that identify people from their voices, and the design and construction of speaker recognition systems has been a fascinating enterprise pursued over many decades. This paper introduces speaker recognition in general and discusses its relevant parameters in relation to system performance.